Perekonomian Pada Masa Al-Khulafa’ Al-Rasyidin - Rahma Aulia Hasanah; Rodiatul Husna; Gafa Anjasya; Fikri Azka Tanjung; Masleni Nasution (STIKes Ibnu Sina Ajibarang, 2024)
This article was written against the background that the economic system is very important for social organization, and economic development is the most important factor in realizing the economic prosperity of society. A healthy economy creates a strong country that can achieve the goals of the economic system according to existing capabilities through continuous struggle between the government and its people. This study aims to identify the role of the Rashidun Caliphate as head of government in economic development and to determine the conditions for economic development under the leadership of the Rashidun Caliphate. Four Companions of the Prophet: Abu Bakar Ash-Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, led Khulafaur Rasyidin. Rasyid Khulafah's economic policies are included in the history of Islamic economic thought. Based on research on economic development during the Khulafah Rasyidin era, the roles of heads of state and government in economic development include 1) running business in accordance with Islamic covenants, 2) requiring Muslims to pay zakat, 3) providing aid. jizyah for the poor, 4) formation of several sections, and so on.